Walking for water and fuelwood: Welfare implications for women and children in Ghana - Lambon-Quayefio, M.P. (Journal of International Development, 2023)
In most sub-Saharan African (SSA) countries, the burden of collecting fuelwood and water is gendered. Competing needs for women's time compel them to make choices, which present challenges for poverty reduction. The study investigates the impact of women's limited access to clean fuel and water on children's and women's welfare outcomes using the third wave of the Ghana socio-economic panel survey. An instrumental variable approach is employed to address the endogeneity of women's time allocation and results suggest that limited access to safe water and clean fuel has significant implications for children's human capital development. I find similar negative effects for women's own health and labour market outcomes. Findings from the study have important policy implications regarding the provision of basic infrastructure for improved welfare outcomes.
Research Article
Keywords: Ghana; labour; unpaid work; health